Revision of the nearctic species of the Cicindela sylvatica group (Coleoptera: Cicindelidae) - Spanton, Timothy Gordon (My University, 1983)
Interspecific and intraspecific variation of C. longilabris Say and C. nebraskana Casey were studied by means of discriminant analysis of morphometric data and univariate analysis of qualitative characters of adult specimens. The geographic variation of male and female genitalic structures of C. longilabris and C. nebraskana was studied and compared with that of the Palearctic species of the sylvatica group: C. sylvatica Linnaeus, C. granulata Gebler, C. japana Motschulsky, C. gemmata Faldermann, C. soluta Dejean and C. lacteola Pallas. Soil associations of the two Nearctic species were investigated. C. longilabris is a boreal and montane forest species occurring on Podzolic soils in eastern North America and Luvisolic and Brunisolic soils of coniferous forests in western North America as well as in boreal forest-grassland transition areas. Three subspecies are recognized: c. l. longilabris Say, found across the boreal zone from Newfoundland and New England to Alaska, C. l. laurentii Schaupp, in the Rocky mountain areas of the United States, including isolated populations in northern New Mexico, eastern Arizona, northern Arizona and southwestern Utah, and c. l. perviridis Schaupp, found in the Sierra Nevada and Cascade Mountains of California, Oregon and Washington. An area of hybridization occurs in southwestern Alberta, southeastern British Columbia, eastern Washington, Idaho and northwestern Montana where the three subspecies converge geographically. C. nebraskana is a monotypic species which occurs on Chernozemic soils of prairie grasslands and grassland-forest transition zones of western North America. The three year life cycle of C. longilabrls is described. Two winters are passed in the larval stage and one winter in the adult stage before mating and oviposition occur. The egg stage and first, second and third stage larvae of c. longilabris are described. A reconstructed phylogeny is presented in which three species pairs are evident, C. soluta-C. gemmata, C. sylvatica-C. granulata, and C. longilabris-C. nebraskana with C. japana being most closely related to the soluta-gemmata sibling species, and C. lacteola having been derived earlier in the evolution of the whole group.
Keywords: Tiger beetles; Beetles North America; Cicindela sylvatica